Daily Price Reversal: A Market Microstructure Explanation Using Bid-Ask Spreads - Hautala, Harri (My University, 2003)
The purpose of this study is to test whether stock prices are reversed after large one-day price changes. The hypotheses consider the sample selection bias due to bid-ask bounce and systematic trading patterns as possible explanations for the phenomenon. The data comprises daily closing bid and ask prices and the last transaction price of all the high-priced stocks listed on the main list of the Helsinki Stock Exchange during the period of 1996-2002. Stocks with a daily return greater than 10 percent are included in the sample of price increase events and stocks with a daily return less than 10 percent are included in the sample of price decrease events. The variation of stocks returns following these extreme price movements is studied using the event study methodology where the abnormal returns are estimated with the market model. The sample selection bias due to bid-ask bounce is investigated using two sample selection criteria for large daily price changes: mid-price returns and closing price returns. The role of systematic trading patterns around the events is studied by calculating the abnormal returns from average bid-ask prices and closing transaction prices for both the samples selected. The results show that, on average, prices are reversed on the following day after the price decrease events. This is, however, explained by the sample selection bias due to bid-ask bounce. No signs of systematic trading patterns are found. This evidence does not support the market mispricing models concerning short- and long-term price reversal. On the other hand, it is neither consistence with agency rationality and market efficiency since stock prices are reported to adjust only partially to the large one-day price decrease events.
Keywords: Price reversal; market microstructure; bid-ask spread; sample selection bias; systematic trading patterns; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|